Teman musafir. - Brunei. Jabatan Mufti Kerajaan ([Bandar Seri Begawan] : Jabatan Mufti Kerajaan, Jabatan Perdana Menteri, Negara Brunei Darussalam, 2013)
On all aspects of travel according to Islamic custom and practice.
In Malay.
Keywords: Travel -- Religious aspects -- Islam